In silico prediction of conserved ortholog set (COS) sequences from Ipomoea batatas - Solís Calero, Christian (2008)
We develop some bioinformatics procedures to predict Conserved Ortholog Set (COS) sequences from Ipomoea batatas, and evaluate their usefulness for molecular markers and diversity studies of this species. We predict orthology relationship between Ipomoea batatas ESTs sequences and Arabidopsis thaliana COS sequences, according to Best Bidirectional Hits (BBHs) criteria, realizing similarity comparison using BLAST X and TBLASTN programs. We obtained a set of 204 putative COS sequences, 16 of them belonged to storage roots. Functional annotation of sweet potato predicted sequences COS was realized using BLASTX, INTERPROSCAN and PSI-BLAST programs. We evaluate possible polymorphisms in COS candidate sequences, finding SNPs in eight sequences and tandem repeats in one of them.